A 122 GHz ISM-Band FMCW Radar Transceiver - Lammert, Vincent; Achatz, S.; Weigel, Robert; Issakov, V. (GeMIC 2020 - Proceedings of the 2020 German Microwave Conference, 2020)
In this work we present a 122 GHz FMCW radar module. It is based on an integrated transceiver in a 130nm SiGe technology. The chip is bonded to a PCB which contains the baseband circuits and the antennas. This paper discusses the design of the whole system around the transceiver IC, chip-to-PCB transition and the PCB antenna array. Finally, measurement results of a target at a distance of 6m are shown.
CRIS-Team Scopus Importer:2020-06-02
Keywords: D-band; ISM-Band; Radar; transceivers

A 122 GHz On-Chip 3-Element Patch Antenna Array with 10 GHz Bandwidth - Lammert, Vincent; Hamouda, Mohamed; Weigel, Robert; Issakov, Vadim (2020 50th European Microwave Conference, EuMC 2020, 2021)
This paper presents the design and measurements of a 122 GHz on-chip patch antenna array in a 130 nm SiGe BiCMOS technology. The array is formed by three rectangular patches in the top metallization layer with the ground plane in the lowest layer. Slots in the patches create a dual-resonance, which helps achieving a simulated bandwidth of 10 GHz and 28% radiation efficiency. The effects of fill structures between the patches and the ground plane are taken into consideration by introducing an equivalent dielectric constant. This makes the array fully compliant with metal density design rules of modern semiconductor processes, while maintaining good performance over a high bandwidth, which makes it attractive for numerous wideband applications, e.g. high-resolution short range radar or high data rate communications.
CRIS-Team Scopus Importer:2021-03-05
Keywords: D-Band; fill structures; metal density; On-chip antenna; patch array; SiGe BiCMOS; wideband

An Integrated 28 GHz Front-End Module for 5G Applications in 45 nm PD-SOI - Ciocoveanu, Radu; Lammert, Vincent; Weigel, Robert; Issakov, Vadim (2019 IEEE MTT-S International Microwave Conference on Hardware and Systems for 5G and Beyond, IMC-5G 2019, 2019)
This paper presents an integrated 28 GHz front-end module (FEM) for 5th Generation (5G) applications and fabricated in a 45 nm partially depleted silicon on insulator (PD-SOI) technology. In transmit (Tx) mode at 28 GHz, the measured saturated output power (Psat), maximum power-added efficiency (PAEmax), output-referred 1-dB compression point (OP1dB) are 17.2 dBm, 26 % and 16.7 dBm, respectively, with 86.4 mW dc power consumption from a 1.8 V supply. In receive (Rx) mode at 28 GHz, the measured gain, noise figure (NF), input-referred 1-dB compression point (IP1dB) are 9dB, 3.6dB and -10dBm, respectively, with 14.8mW dc power consumption from a 1 V supply. The chip core size is 0.62mm x 0.75mm.
CRIS-Team Scopus Importer:2021-04-20

Transformer-Coupled D-Band PA with 11.8 dBm Psat and 6.3 % PAE in 0.13 μm SiGe BiCMOS - Romstadt, Justin; Lammert, Vincent; Pohl, Nils; Issakov, Vadim (2020 IEEE 20th Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems, SiRF 2020, 2020)
In this paper we present a fully differential power amplifier (PA) in a 0.13 μm SiGe BiCMOS technology operating in D-Band. The PA has a maximum PAE of 6.3 %, a saturated output power of 11.8 dBm at a frequency of 114 GHz and is designed to an optimum load impedance different from 50 Ω offered by a chip to PCB transition. In the previously designed SiGe BiCMOS PAs for D-Band applications, interstage matching networks consist of transmission lines, whereas in this work a transformer is used because a transformer offers the advantage of being an efficient and compact higher-order filter. Therefore, the amplifier only occupies an active chip area of 0.19 mm2 including baluns. In CMOS transformer-based coupling between the stages is quite common, whereas in SiGe this has not been demonstrated so far. Accordingly, to the authors best knowledge, this is the first D-Band SiGe PA using transformer-coupling.
CRIS-Team Scopus Importer:2020-04-24
Keywords: D-Band; HBT; Millimeter wave circuits; Power amplifier (PA); Silicon germanium (SiGe); transformer